2018
DOI: 10.11113/jt.v80.10869
|View full text |Cite
|
Sign up to set email alerts
|

Cod and Ammonia Removal From Landfill Leachate Using Mixed Granular Adsorbent Media

Abstract: Landfills generate leachate that contains elevated concentration of contaminants and is hazardous to human health and the ecosystem. In this study, the mixture of granular feldspar and cockle shells was investigated for remediation of COD and ammonia from landfill leachate. All adsorbent media were sieved to a particle size between 2.00 and 3.35 mm. The results revealed that the optimum mixing ratio of feldspar and cockle shells was 20:20, shaking speed was 150 rpm, pH level was 6, shaking time was 120 min, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…Therefore, the dominant adsorption mechanism can be described to be chemisorption. The result is also consistent with that in literature which reported that the reaction kinetics of similar media followed the psudo-second order model [23,24,25,26,27]. The pseudo-first order and pseudosecond order rate constants (K 1 and K 2 ) were 0.0397 and 0.1300 respectively.…”
Section: Adsorption Kineticssupporting
confidence: 92%
“…Therefore, the dominant adsorption mechanism can be described to be chemisorption. The result is also consistent with that in literature which reported that the reaction kinetics of similar media followed the psudo-second order model [23,24,25,26,27]. The pseudo-first order and pseudosecond order rate constants (K 1 and K 2 ) were 0.0397 and 0.1300 respectively.…”
Section: Adsorption Kineticssupporting
confidence: 92%
“…The model expressions were selected in accordance to successive model sum of squares and is based on polynomial's highest order. The relation between the actual and predicted experimental data was significant as demonstrated by the model's actual R 2 value of 0.9815 for COD and which were relatively close to the predicted R 2 value of 0.9230 [16] (3)…”
Section: Establishment Of Regression Model Equations Using Ccdsupporting
confidence: 57%
“…The developed model terms which have value of Prob. > F less than 0.05 are significant while the converse is insignificant [16]. With regards to COD percentage removals, apparently from Table 4, the model F value obtained is 68.27 and the Prob.…”
Section: Discussionmentioning
confidence: 78%
“…Water deficiency and contamination currently rank evenly with climate change as the most pressing environmental perturbation [1][2][3][4][5][6][7][8]. Due to increasing globalization and urbanization, which intensify ecological damage and severely endanger human health and the environment, adsorption, especially for the use of activated carbons and zeolites has been the focus of numerous studies and it is extensively applied to wastewater management [9][10][11].…”
Section: Introductionmentioning
confidence: 99%